2022
DOI: 10.1021/acs.jafc.2c03870
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analysis of Transcriptome and Metabolome Reveals the Potential Mechanism of the Enantioselective Effect of Chiral Penthiopyrad on Tomato Fruit Flavor Quality

Abstract: This study investigated the enantioselective effects of S-, R-, and rac-penthiopyrad (PEN) on the flavor quality of tomato fruit through the levels of sugars, acids, volatiles, and nutrients and explored the potential mechanism by combined analysis of the transcriptome and metabolome. The results revealed that the S-enantiomer increased the content of soluble sugars while decreasing the content of organic acids, thereby increasing the taste of tomato fruit. Furthermore, S-(+)-PEN promoted the accumulation of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In addition, the TCA cycle serves as a hub for the metabolic linkage and interconversion of carbohydrates and amino acids, and its metabolic production of organic acids such as citric acid directly determines the acidity of the fruit. 47 In this study, ES treatment downregulated the levels of metabolites succinic acid, fumaric acid, isocitrate, and citric acid in blueberry fruits under soil Cd toxicity, which may be an important factor in the decreased TA in blueberry fruits (Figures 1H and 5B). Similarly, ESs can respond to abiotic stresses by regulating fruit organic acid accumulation or consumption.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In addition, the TCA cycle serves as a hub for the metabolic linkage and interconversion of carbohydrates and amino acids, and its metabolic production of organic acids such as citric acid directly determines the acidity of the fruit. 47 In this study, ES treatment downregulated the levels of metabolites succinic acid, fumaric acid, isocitrate, and citric acid in blueberry fruits under soil Cd toxicity, which may be an important factor in the decreased TA in blueberry fruits (Figures 1H and 5B). Similarly, ESs can respond to abiotic stresses by regulating fruit organic acid accumulation or consumption.…”
Section: Discussionmentioning
confidence: 49%
“…Glutathione plays an active role in antioxidant and detoxification in plants, and the glutathione levels in blueberry fruits were significantly increased under Spd, EBR, and MT treatments (Figure D), suggesting that ESs can enhance the tolerance of blueberry fruits to soil Cd toxicity. In addition, the TCA cycle serves as a hub for the metabolic linkage and interconversion of carbohydrates and amino acids, and its metabolic production of organic acids such as citric acid directly determines the acidity of the fruit . In this study, ES treatment downregulated the levels of metabolites succinic acid, fumaric acid, isocitrate, and citric acid in blueberry fruits under soil Cd toxicity, which may be an important factor in the decreased TA in blueberry fruits (Figures H and B).…”
Section: Discussionmentioning
confidence: 51%
“…Metabolic pathway analysis was performed using MetaboAnalyst 5.0. The pathway with p value < 0.05 was considered to be a differential metabolic pathway [52].…”
Section: Untargeted Metabolomics Analysismentioning
confidence: 99%
“…In fact, there are many studies that have shown that some fungicides have adverse effects on plant growth and fruit quality. Liu et al found that R-penthiopyrad increased the content of organic acids in tomato fruit, thus reducing the sugar–acid ratio and making the fruit taste worse . It was reported that the application of difenoconazole reduced the content of amino acids and total phenols in tea and changed the volatile profiles …”
Section: Introductionmentioning
confidence: 99%
“…Liu et al found that R-penthiopyrad increased the content of organic acids in tomato fruit, thus reducing the sugar−acid ratio and making the fruit taste worse. 13 It was reported that the application of difenoconazole reduced the content of amino acids and total phenols in tea and changed the volatile profiles. 14 Based on previous studies, these two fungicides may have adverse effects on fruit quality.…”
Section: Introductionmentioning
confidence: 99%